Agro And Eco-Tourism Development In Rural Areas Of Uzbekistan: Analysis Using Of “Gravity” Model Approach - Togaymurodov Elbek; Islomova Risolat; Stamatis Aggelopoulos (European Scientific Journal, ESJ, 2016)
The main purpose of the article is formulation of ways and favorable conditions and possibilities for development of agro and eco-tourism in rural areas of Uzbekistan. At the same time, inflow of tourists using approach of “Gravity” model was analyzed in order to identify theoretical and practical aspects of alternative identification of the share of tourism services in contemporary development of rural areas and agriculture of Samarkand region. Within the framework of our research, we studied theoretical and practical aspects of agro and eco-tourism and the rural areas of Samarkand region and collected statistical data was analyzed on the basis of “Gravity” model and forecasted indicators of tourism inflow were identified. As the result of the research, scientific and practically significant recommendations have also been developed and figured out.